Quran-Based Islamic Religious Education and Religious Character Formation in the Digital Era - Ummul Khoir; Muhammad Haiful Fudhul; Annas Muhtadi; Yeti Sumiati; Gina Farhanah Jauza (Journal of Social Work and Science Education, 2026)
This study examines the concept, implementation strategies, teacher roles, impacts, and challenges of Quran-based Islamic Religious Education (PAI) in shaping students’ religious character in the digital era. Employing a qualitative descriptive field study design, data were collected through participant observation, in-depth interviews with PAI teachers and school administrators, and document analysis. Data analysis followed the Miles and Huberman interactive model, comprising data reduction, data display, and conclusion drawing. The findings indicate that thematic and contextual Quran-based PAI learning enhances students’ spiritual awareness, moral values, religious discipline, and moderate religious attitudes. The integration of Quranic values influences not only cognitive understanding but also the internalization of moral and spiritual values reflected in students’ daily behavior, including their use of digital media. This study offers novelty by identifying adaptive strategies that position Quran-based PAI learning as an ethical filter for addressing moral challenges in the digital age. The findings contribute to Islamic education theory and highlight the importance of pedagogical reform through teacher role modeling, value habituation, and reflective learning practices.